Livestock ownership and management in the Chibi and management communal areas of Zimbabwe - Mombeshora, B.; Agyemang, K.; Wilson, R.T. (International Livestock Centre for Africa, 1985)
Formal surveys were carried out in two communal areas in Zimbabwe. In the dry south-east lowlands, 72 percent of farmers owned at least one species of livestock, while in the better endowed central area 84 percent owned animals. More than 25 percent of farmers in both areas owned two or more species. Cattle are kept mainly to provide draught power: the use of cows as draught animals is common. Donkeys are an important source of draught in the drier area. Crop residues contribute to animal feed supplies in the dry season. Winter ploughing is practised by about 50 percent of farmers. There are significant relationships between number of animals owned and household size, number of implements and area of maize, but not between animals and total area cultivated.